Hubungan Kemampuan Numerik Dan Kemampuan Verbal Siswa dalam Pembelajaran Matematika - Andi Quraisy (Journal of Mathematics: Theory and Applications, 2022)
This research was conducted with the aim of knowing the relationship or correlation between numerical abilities and verbal abilities of UPTD students at SMP Negeri 3 Sinjai. This study is a quantitative research with a research sample of 67 students. The sampling method used is Cluster Random Sampling. The data collection technique in this study used a numerical ability questionnaire and a verbal ability questionnaire. Data were analyzed by descriptive statistics and inferential statistics using correlation analysis. The results indicated that the average value of students' numerical ability was above the value of verbal ability, namely 68.05 for numerical ability and 55.68 for verbal ability, while based on the results of the calculation of correlation analysis techniques, the correlation coefficient value (r) was 0.33. The correlation of the two variables is in the weak category. These results suggest that there is a significant positive relationship between numerical ability and verbal ability. The higher the numerical ability, the higher the verbal ability. Conversely, the lower the numerical ability, the lower the verbal ability.